MEMBUMIKAN RISET DALAM PROGRAM LITERASI MAN 5 JOMBANG : MEMBUMIKAN RISET DALAM PROGRAM LITERASI MAN 5 JOMBANG - Kiswati; Dianita, Tri (Al Tadib : Jurnal Ilmu Pendidikan, 2020)
Abstract: This article aims to describe the best practice done by MAN 5 Jombang in activate the research program in that school which was not active anymore for years. As â€œMadrasah Literasiâ€, MAN 5 Jombang tries to hold some activity that enhance reading and writing interest of students, such as reading corner, book summary and extensive reading for reading activity. Book as Bridges, wall magazine writing, workshop on writing article and visiting research school are the efforts of MAN 5 Jombang to improve the writing interest of the students.Finally those activity hopefully can be the embryo of the reborn of the research program of MAN 5 Jombang that was successful until national level years ago.